Analysis of financial resources for public health in Brazilian capitals: a time trend ecological study - Vinícius Henrique Ferreira Pereira de Oliveira; Millena Barroso Oliveira; Cauane Blumenberg; Álex Moreira Herval; Luiz Renato Paranhos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
This study aimed to analyze part of the financial resources used to fund public health actions in the 26-Brazilian capitals, from 2008 to 2018. This is a time-trend ecological study involving revenue and expenditure indicators provided by the Information System on Public Budget for Health (SIOPS). The values were deflated based on the Extended National Consumer Price Index of 2018 in Brazil to allow the comparison over the years. The mean annual variation of health investments, in Brazilian Reais (BRL) was assessed using linear regressions. Pearson's correlation coefficients were estimated between federal revenues and expenditures with the capitals' resources. All capitals presented statistically significant positive correlations for the origin of the budget resource invested in health. The lowest coefficient was found in the capital city of Macapá (Amapá State) (r = 0.860) and the highest, in Fortaleza (Ceará State) (r = 0.997). Belo Horizonte (Minas Gerais State) was the capital with the highest annual increase in federal transfers (about BRL 67.91 per year) and Teresina (Piauí State) presented the highest annual increase in health expenditures among the capitals (about BRL 55.42 per year). We found a increase in the transfers of the Brazilian Unified National Health System (SUS) and municipal resources in almost all capitals, but there are still inequalities in the distribution of financial resources among Brazilian capitals from different regions. Health funding is affected by the municipalization of SUS and it is not the single factor affecting the access and quality of health services.